From Acute Injury to Return to Play: A Comprehensive Review of Biomechanical Principles and Current Strategies in the Diagnosis, Treatment, and Rehabilitation of Acute and Chronic Ankle Ligament Injuries in Sporting Populations. - Dobosz, Gabriela; Hobot, Mikołaj; Przybylska, Zuzanna; Purpura, Aleksandra; Rolski, Wiktor; Michalska, Paulina; Przystaś, Bartłomiej; Grzechowiak, Magdalena; Podeszwa, Sebastian (Quality in Sport, 2026)
Background. Lateral ankle sprains (LAS) are the most frequent musculoskeletal injuries in sports medicine, often leading to chronic ankle instability (CAI). Despite their prevalence in disciplines like basketball or soccer, mismanagement remains common, resulting in long-term sensorimotor deficits and joint degeneration. Modern paradigms are currently shifting from traditional immobilization toward proactive functional mobilization and advanced surgical interventions. Aim. This review synthesizes contemporary clinical evidence and biomechanical principles to establish a standardized management algorithm for athletes with acute and chronic lateral ligamentous lesions. Material and Methods. A comprehensive analysis of forty peer-reviewed studies published up to early 2025 was conducted. The synthesis prioritizes diagnostic precision, biomechanical strain patterns, and the comparative efficacy of surgical versus functional rehabilitation interventions in competitive sporting populations. Results. Precise injury grading, ideally performed five days post-injury, increases diagnostic sensitivity to over 90%. High-resolution dynamic ultrasonography offers superior assessment of functional instability compared to static MRI. Implementation of the "PEACE and LOVE" framework results in faster return-to-play timelines than traditional rest. In elite sports, arthroscopic "all-inside" repairs reinforced with InternalBrace augmentation maintain recurrence rates below 5%. Conclusions. Optimizing athletic recovery requires a multidisciplinary algorithm bridging mechanical healing and functional homeostasis. Precise injury grading, early functional loading, and biologically reinforced repairs are vital for long-term joint integrity and career longevity.